IMPROVING ORGANIZATIONAL CITIZENSHIP BEHAVIOR THROUGH ORGANIZATIONAL JUSTICE AND JOB SATISFACTION - Hendra Hendra; Shofia Amin; Rike Setiawati (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
This study examined how to improve organizational citizenship behavior (OCB), organizational justice, and job satisfaction. 85 employees of the Regional Finance Institution of Tanjung Jabung Regency, Jambi Province, were respondents in this study through the distribution of questionnaires. Hypothesis testing is carried out using smart PLS version 3.0. The findings showed a significant effect between organizational justice and job satisfaction, between Organizational justice and OCB, and between Job satisfaction and OCB. Thus, Job satisfaction only acts as a partial mediation. This finding indicates that organizational justice and job satisfaction can directly influence the increase in OCB without going through the mediator variables. Therefore, improving OCB can be done by directly enhancing the perception of organizational justice and directly improving job satisfaction.